Rare circle of Willis variants associated with multiple intracranial aneurysms and subarachnoid hemorrhage - Mohamad H. Mosi; Hisham Alfarra; Nawwar Soliman; Moaaz Khalouf Alshaar; Mahmoud Khalouf Alshaar; Ghassan Hamzeh (Medicine, 2026)
Rationale: Subarachnoid hemorrhage from a ruptured intracranial aneurysm is a type of stroke with high rates of mortality and disability, and the prevalence of aneurysm formation increases in the presence of Circle of Willis variants. Patient concerns: A 64-year-old man with a history of hypertension and psoriatic arthritis presented with a sudden severe headache and walking difficulties without any loss of consciousness. Diagnoses: Non-contrast computed tomography showed a diffuse subarachnoid hemorrhage. Computed tomography angiography demonstrated multiple intracranial aneurysms together with variants of the posterior communicating artery and posterior cerebral artery, which may have contributed to aneurysm formation. Interventions: The patient was started on oral Nimodipine to prevent cerebral vasospasm and underwent stent-assisted coil embolization of the ruptured aneurysm. Outcomes: His symptoms and clinical condition improved a few days after the embolization, and he was discharged after 18 days. Lessons: This is the first documented case report from Syria, and possibly the first ever, detailing such Circle of Willis variants associated with cerebral aneurysms. It underscores the need for further studies exploring the relationship between the type of variants and the number and size of cerebral aneurysms, which is important for a better understanding of the epidemiology of cerebral aneurysms.